1986
DOI: 10.1159/000146137
|View full text |Cite
|
Sign up to set email alerts
|

Langerhans Cells in Murine Vaginal Epithelium Affected by Oestrogen and Topical Vitamin A

Abstract: Langerhans cells vary in their morphology and distribution in the vaginal epithelium of ovariectomized mice stimulated to hyperplasia and keratinization by oestrogen. When the stratum corneum was removed by topical vitamin A application, the shape and distribution of Langerhans cells were unaffected. It was concluded that Langerhans cell morphology and distribution depend on the configuration of the lower strata of the epithelium and not on the presence of a stratum corneum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…9,10 The pleotropic effects of estrogen on the epithelium of the reproductive tract are thought to facilitate and enhance C. albicans adhesion, growth and colonization. 8,11,12 Several investigators have used estrogen in conjunction with C. albicans vaginal inoculation to construct animal models of persistent VC; among these models is the estrogen-dependent VC (EDVC) murine model. [13][14][15] This model has proved to be useful in evaluating the various aspects of pathogenesis of VC as VC in the absence of estrogen treatment in the murine system is transient and only lasts for few days.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 The pleotropic effects of estrogen on the epithelium of the reproductive tract are thought to facilitate and enhance C. albicans adhesion, growth and colonization. 8,11,12 Several investigators have used estrogen in conjunction with C. albicans vaginal inoculation to construct animal models of persistent VC; among these models is the estrogen-dependent VC (EDVC) murine model. [13][14][15] This model has proved to be useful in evaluating the various aspects of pathogenesis of VC as VC in the absence of estrogen treatment in the murine system is transient and only lasts for few days.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, estriols, pregnanediols, pregnanetrials and estradiols have been shown to increase germination of C. albicans 9,10 . The pleotropic effects of estrogen on the epithelium of the reproductive tract are thought to facilitate and enhance C. albicans adhesion, growth and colonization 8,11,12 . Several investigators have used estrogen in conjunction with C. albicans vaginal inoculation to construct animal models of persistent VC; among these models is the estrogen‐dependent VC (EDVC) murine model 13–15 .…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon also occurs in rat (Parakkal, 1974;Centola, 1978;Vijayasaradhi & Gupta, 1987) and mouse (Allen, 1927;Young & Hosking, 1986;Nelson et al, 1991;Horvat et al, 1992). The acquisition of secretory activity, changes in the pattern of keratinization, and an increase in the rate of mitosis were also seen.…”
Section: Discussionmentioning
confidence: 79%
“…Sex hormones may also directly influence DC/LC by modulating their morphology, density, distribution, maturity and function (Kaushic et al, 1998;Komi et al, 2001;Koyama et al, 1989;Wira et al, 2000;Young and Hosking, 1986). More specifically, sex hormones have been shown to influence the distribution of DC in the epithelium of rat reproductive tract (Kaushic et al, 1998).…”
Section: Role Of Sex Hormones On the Cervical Immune Microenvironmentmentioning
confidence: 99%